2020
DOI: 10.3390/polym12061429
|View full text |Cite
|
Sign up to set email alerts
|

Development of Polypropylene-Based Single-Polymer Composites With Blends of Amorphous Poly-Alpha-Olefin and Random Polypropylene Copolymer

Abstract: We developed polypropylene-based single-polymer composites (PP-SPC) with blends of amorphous poly-alpha-olefin (APAO) and random polypropylene copolymer (rPP) as matrix material and polypropylene (PP) woven fabric as reinforcement. Our goal was to utilize the lower melting temperature of APAO/rPP blends to increase the consolidation of the composites and decrease the heat load of the PP reinforcement. We produced the composites by film-stacking at 160 °C, and characterized the composites with density, peel, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…According to the recommendations, VP 792 and VP703 might improve the elongation at break of the blend [34].…”
Section: Resultsmentioning
confidence: 99%
“…According to the recommendations, VP 792 and VP703 might improve the elongation at break of the blend [34].…”
Section: Resultsmentioning
confidence: 99%
“…For example, low-molecular-weight amorphous random aPP has been used as a toughness agent for isotactic iPP. 24,25 Actually, a few of LMWPs, specifically monosaccharides, such as glucose with glycerol have been used in starchbased materials as plasticizers or toughness agents. 20,26−28 For example, Zhang and Han 20 have found that polyol-plasticized films had lower T g than the monosaccharide-plasticized (glucose, mannose, and fructose).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The concept of the application of low molecular weight chemicals with the same chemical compounds as toughness agents has been developed previously. For example, low-molecular-weight amorphous random aPP has been used as a toughness agent for isotactic iPP. , Actually, a few of LMWPs, specifically monosaccharides, such as glucose with glycerol have been used in starch-based materials as plasticizers or toughness agents. , For example, Zhang and Han have found that polyol-plasticized films had lower T g than the monosaccharide-plasticized (glucose, mannose, and fructose). Recently, Gao et al studied the co-plasticizer of glycerol with sugar and found that the relative crystallinity of the films decreased after the addition of sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Bumper covers due to traffic accidents are considered the most commonly replaced car body parts [ 4 ]. Most polymer bumpers are based on glass fiber-reinforced composites, using polypropylene (PP) or other plastics such as polycarbonate (PC), polycarbonate (PC)/polybutylene perephthalate (PBT), and rubber toughened PP as the matrix [ 6 , 7 , 8 , 9 ]. Bumper bars are generally designed to absorb impact energy generated from low-speed impacts (toughened polyolefin (PO) blends or even polyurethane (PU)) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%